2006
DOI: 10.5194/acp-6-2273-2006
|View full text |Cite
|
Sign up to set email alerts
|

Interactive chemistry in the Laboratoire de Météorologie Dynamique general circulation model: model description and impact analysis of biogenic hydrocarbons on tropospheric chemistry

Abstract: Abstract. We present a description and evaluation of LMDz-INCA, a global three-dimensional chemistry-climate model, pertaining to its recently developed NMHC version. In this substantially extended version of the model a comprehensive representation of the photochemistry of non-methane hydrocarbons (NMHC) and volatile organic compounds (VOC) from biogenic, anthropogenic, and biomass-burning sources has been included. The tropospheric annual mean methane (9.2 years) and methylchloroform (5.5 years) chemical lif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
254
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(264 citation statements)
references
References 143 publications
(150 reference statements)
9
254
0
1
Order By: Relevance
“…Together, these three models form the LMDz-OR-INCA model. Fundamentals for the gas phase chemistry are presented in Hauglustaine et al (2004) and first results with the full tropospheric gaseous chemical scheme are gathered by Folberth et al (2006). The oxidative tropospheric photochemistry is described through 85 chemical species and 264 chemical reactions, including non-methane hydrocarbon oxidation.…”
Section: Methodology and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these three models form the LMDz-OR-INCA model. Fundamentals for the gas phase chemistry are presented in Hauglustaine et al (2004) and first results with the full tropospheric gaseous chemical scheme are gathered by Folberth et al (2006). The oxidative tropospheric photochemistry is described through 85 chemical species and 264 chemical reactions, including non-methane hydrocarbon oxidation.…”
Section: Methodology and Modelsmentioning
confidence: 99%
“…The assessment of the long-term trends induced by the use of the historical anthropogenic emission datasets in global chemical models is discussed in Lamarque et al (2010) and is not tackled in this paper. The historical trends of total aerosols contents and global tropospheric ozone compared to those described in Cionni et al (2011) and Lamarque et al (2011) In order to use these fluxes in the INCA model, we reported the individual hydrocarbon fluxes on INCA species or surrogate species as described in Folberth et al (2006), we spatially interpolated the fluxes to the model resolution (3.75°9 1.9°) and we applied a linear interpolation between decades. The methane oxidation is computed interactively according to the emissions and not prescribed on concentrations as often made in such exercises (e.g.…”
Section: Lmdz-or-inca Set-upmentioning
confidence: 99%
“…Simpson, 1995;Roberts et al, 2006; or the composition of the global troposphere (e.g. von Kuhlmann et al, 2004;Folberth et al, 2006;Fiore et al, 2011). By exploiting the sensitivity studies described in Sect.…”
Section: The Influence Of Bvoc Emissions On Global Tropospheric Compomentioning
confidence: 99%
“…M. Fiore et al: North American isoprene influence on intercontinental ozone pollution have been shown to enhance the tropospheric O 3 burden (e.g., Fuentes et al, 2000;Folberth et al, 2006;Wild, 2007;Wu et al, 2007;Pfister et al, 2008). In the eastern United States, July isoprene emissions have been estimated to be 4 to over 10 times higher than anthropogenic NMVOC (e.g., Fiore et al, 2005).…”
mentioning
confidence: 99%